The Effect of Wadiah Savings and Wadiah Current Accounts on the Profitability of Sharia Commercial Banks in Indonesia - Mochammad Ainur Rozikin; Guntur Kusuma Wardana (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2025)
Profitability is a crucial indicator of a bank's success in performing its intermediary function in managing public funds. Therefore, Islamic commercial banks need to continually enhance their profitability. Factors such as wadiah savings and wadiah current accounts are considered to contribute to sustainable profitability, as they reflect the bank’s ability to manage financial risks, meet obligations, and optimize asset utilization. This study aims to analyze the effect of wadiah savings and wadiah current accounts on the profitability of Islamic commercial banks in Indonesia, using profit-sharing financing and non-profit-sharing financing as control variables. This research employs a quantitative descriptive method. The population consists of 14 Islamic commercial banks registered with the Financial Services Authority (OJK) in 2024, from which 8 banks were selected using purposive sampling. The study uses secondary data obtained from annual financial reports of each bank during the 2013–2024 period. Data analysis was conducted using the panel data regression method with EViews 13. The results show that wadiah savings and wadiah current accounts partially and simultaneously have a significant effect on the profitability of Islamic commercial banks in Indonesia.